FAKTOR- FAKTOR YANG MEMPENGARUHI FINANCIAL PERFORMANCE PADA PERUSAHAN CONSUMER GOODS - Gabriella Fortunata; Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2023)
This research aims at how the effect of liquidity, intellectual capital, company size, company age toward financial performance on consumer goods industry listed on the Indonesia Stock Exchange during 2017-2019. The sample on this research was selected using purposive sampling method and the qualified data was 27 companies. Data processing techniques using multiple regression analysis with helped by E-views program series 12 and Microsoft Excel. The results of this study indicate that liquidity and company age has significant positive effect on financial performance. However intellectual capital has no significant positive effect on financial performance, and company size has no significant negative effect on financial performance.